Physical science teachers’ perspectives on professional development and use of digital technology - Dlamini, Maserialong; Jita, Thuthukile (Edelweiss Applied Science and Technology, 2024)
This paper examines physical science teachers’ views and experiences on professional devel-opment and digital technology integration for teaching content specific. Using a qualitative ap-proach and case study design embedded in the technological pedagogical content knowledge (TPACK) model and concerns-based adoption model (CBAM), this article reports on how physi-cal science teachers from technologically resourced schools perceive their preparation to use technology during professional development. Four participants with more than three years teaching experience of physical science were selected for data collection. Data was collected through semi-structured interviews and was thematically analyzed. The key findings of the study indicate that inadequate digital technology professional development leads to teachers’ unpreparedness which tremendously influences the extent of using technology for teaching in physical science content. The paper recommends the need for ongoing professional develop-ment of physical science teachers on the use of digital technology to teach specific content. Based on the existing literature, the principles of effective professional development can be used to narrow inequalities in developing countries such as Lesotho. The paper recommends future research to investigate the maximum effectiveness of technology integration in other subjects as to improve teaching and learning in developing countries such as Lesotho.